ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMA PADA BEBERAPA SEKOLAH DI KOTA MEDAN - Merry Tobing; Roulina Purba; Agustiani Simbolon; Zakirah Anjani; Mariati Purnama Simanjuntak (STKIP Subang, 2026)
Critical thinking is an important 21st-century skill to develop in physics learning because it helps students understand concepts, analyze problems, and make decisions based on logical reasoning. However, students' critical thinking remains a concern in the learning process, so a study is needed to obtain an overview of this ability in various school conditions. This study aims to describe students' critical thinking abilities in physics learning in three different high schools based on critical thinking indicators according to Facione, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. This study uses a descriptive method with a qualitative approach. The research subjects consisted of physics teachers and 11th-grade students at the three schools that were the research locations. Data were collected through observation, interviews, documentation, and critical thinking ability tests in the form of essay questions. Data were analyzed descriptively to obtain an overview of students' critical thinking abilities in each school. The results showed that students' critical thinking abilities in the three schools were generally in the moderate category. The highest average critical thinking ability was obtained by SMA B at 66.5, followed by SMA A at 62, and SMA C at 58.8. The interpretation, evaluation, and inference indicators showed better performance than the analysis and self-regulation indicators, which tended to be lower. The research findings indicate that students' critical thinking skills still need to be improved through more student-centered learning, the use of interactive learning media, and the provision of activities that encourage higher-order thinking skills. The results of this study are expected to serve as evaluation material for teachers in designing physics lessons that support the development of students' critical thinking skills.